Original paperThe utility of duplex ultrasound scanning in reporting the vascular complications after heart catheterization performed from new arterial approaches – radial or femoral artery access with StarClose usage – a substudy of the RADIAMI II trial - Kowalczuk, Anetta M.; Chodór, Piotr; Streb, Witold; Kurek, Tomasz; Kalarus, Zbigniew; Zembala, Marian (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Background: RADIAMI II – Radial versus Femoral Approach for Percutaneous Intervention with StarClose Device Using in Patients with Acute Myocardial Infarction was a single center, randomized prospective trial. A substudy of this trial was to evaluate the to utility of duplex ultrasound scanning (DUS) in the patency assessment of the radial or femoral arteries as well as the to evaluate the occurrence of local iatrogenic complications. Aim : To choose the safest method of arterial access in primary coronary angioplasty in ST elevation myocardial infarction (STEMI) by the comparison of both studied groups. Material and methods: The 108 consecutive patients hospitalized from September 2006 to March 2008 with STEMI and qualified to percutaneous coronary intervention (PCI) were randomly assigned to transradial (group I, n = 49) or transfemoral (group II, n = 59) approaches. The DUS protocol was devised and implemented by vascular ultrasound core laboratory with extensive experience in vascular device trials in 5 days after PCI. DUS inguinal region from 6 cm proximal to 6 cm distal to the arteriotomy puncture was performed. A qualitative examination was performed to determine the presence StarClose localization and iatrogenic vascular injuries: major haematoma  5 cm, pseudoaneurysm (PSA), arteriovenous fistula (AVF), and arterial thrombosis or stenosis, using 2-dimensional gray scale, color and focused Doppler images. Results: Duplex ultrasonography of 108 subjects randomized to either group I (n = 49) or group II (n = 59) were performed and evaluated. In both groups there were no evidence of PSA, AVF, stenosis or arterial thrombosis. The hematoma  5 cm was observed in 4 patients of group I whereas in group II such a complication was affirmed in 10 patients (8.16% vs. 16.95%, p = 0.287). Pseudoaneurysm was observed only in patient from the group II (1.69%, p = 0.926). Both groups maintained vessel patency without stenosis, thrombosis, pseudoaneurysm, or AV fistula in follow-up. Conclusions : Duplex ultrasonography is a reliable, safe and accurate method for the assessment the vascular access site complications after invasivly treated patients with STEMI. The study showed that both radial and femoral access followed by StarClose implantation are safe metods of arterial access during PCI.